The Application of Nanotechnology for the Diagnosis and Treatment of Brain Diseases and Disorders - Ngowi, Ebenezeri Erasto; Wang, Yi-Zhen; Qian, Lei; Helmy, Yasmeen Ahmed Saleheldin Hassan; Anyomi, Bright; Li, Tao; Zheng, Meng; Jiang, En-She; Duan, Shao-Feng; Wei, Jian-She; Wu, Dong-Dong; Ji, Xin-Ying (Frontiers in Bioengineering and Biotechnology, 2021)
Brain is by far the most complex organ in the body. It is involved in the regulation of cognitive, behavioral, and emotional activities. The organ is also a target for many diseases and disorders ranging from injuries to cancers and neurodegenerative diseases. Brain diseases are the main causes of disability and one of the leading causes of deaths. Several drugs that have shown potential in improving brain structure and functioning in animal models face many challenges including the delivery, specificity, and toxicity. For many years, researchers have been facing challenge of developing drugs that can cross the physical (blood-brain barrier), electrical, and chemical barriers of the brain and target the desired region with few adverse events. In recent years, nanotechnology emerged as an important technique for modifying and manipulating different objects at the molecular level to obtain desired features. The technique has proven to be useful in diagnosis as well as treatments of brain diseases and disorders by facilitating the delivery of drugs and improving their efficacy. As the subject is still hot and new research findings are emerging, it is clear that nanotechnology could upgrade health care systems by providing easy and highly efficient diagnostic and treatment methods. In this review, we will focus on the application of nanotechnology in the diagnosis and treatment of brain diseases and disorders by illuminating the potential of nanoparticles.